What Was That Brand? Exploring the Vampire Effect in Online Advertising - Soliman, Merna (AUC Knowledge Fountain, 2025)
This study investigates the vampire effect in online advertising, examining how spectacular creative elements can overshadow brand and message recall in digital environments. While previous research has primarily focused on celebrity endorsement in traditional media, this study expands the understanding of the vampire effect by examining four key elements: breathtaking panoramic views, overpowering celebrity endorsements, amazing concepts, and overwhelming jingles. Through an experimental design involving 35 participants exposed to advertisements embedded within digital content, this research demonstrates that all four elements significantly impact brand recall, while celebrity endorsement and amazing concepts also affect message recall. The study employs attention theory and the concept of awe to explain these effects, suggesting that spectacular elements trigger specific cognitive processes that can interfere with brand information encoding. This study contributes to the vampire effect theory by adding three additional dimensions that were not discussed before- overwhelming jingles, amazing concepts, and astonishing panoramic views- as direct causes of the vampire effect. The findings contribute to advertising theory by extending vampire effect research into digital contexts and provide practical implications for managing creative elements in online advertising. Results indicate that integrating brand elements throughout advertisements, rather than treating them as separate components, may help mitigate the vampire effect. This research offers valuable insights for advertising practitioners while highlighting the need for further investigation into platform-specific effects and long-term recall implications.